2010
DOI: 10.1056/nejmoa0909169
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab versus Cyclophosphamide in ANCA-Associated Renal Vasculitis

Abstract: A rituximab-based regimen was not superior to standard intravenous cyclophosphamide for severe ANCA-associated vasculitis. Sustained-remission rates were high in both groups, and the rituximab-based regimen was not associated with reductions in early severe adverse events. (Funded by Cambridge University Hospitals National Health Service Foundation Trust and F. Hoffmann-La Roche; Current Controlled Trials number, ISRCTN28528813.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
898
1
104

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,511 publications
(1,079 citation statements)
references
References 36 publications
27
898
1
104
Order By: Relevance
“…The serious adverse effects of continuous oral cyclophosphamide have been greatly reduced by a pulse regime or by substituting less-toxic immunosuppressive agents for induction and/or maintenance treatment, albeit at the expense of a higher relapse rate. Since publication of the 2010 Peripheral Nerve Society guideline 4 , evidence has shown that rituximab is at least as efficacious as cyclophosphamide for induction of remission and more efficacious than azathioprine in the maintenance of remission in the ANCA-associated vasculitides [142][143][144] . The most up-to-date guidelines on the treatment of the ANCA-associated vasculitides were published by the British Society for Rheumatology in 2014 (REF.…”
Section: Evidence From Systemic Vasculitismentioning
confidence: 99%
“…The serious adverse effects of continuous oral cyclophosphamide have been greatly reduced by a pulse regime or by substituting less-toxic immunosuppressive agents for induction and/or maintenance treatment, albeit at the expense of a higher relapse rate. Since publication of the 2010 Peripheral Nerve Society guideline 4 , evidence has shown that rituximab is at least as efficacious as cyclophosphamide for induction of remission and more efficacious than azathioprine in the maintenance of remission in the ANCA-associated vasculitides [142][143][144] . The most up-to-date guidelines on the treatment of the ANCA-associated vasculitides were published by the British Society for Rheumatology in 2014 (REF.…”
Section: Evidence From Systemic Vasculitismentioning
confidence: 99%
“…Based on the results of open-label studies, two randomized studies were designed to test the efficacy of RTX as induction therapy compared to standard treatment with cyclophosphamide [21] and [22]. The RITUXVAS (RTX versus Cyclophosphamide in ANCA-Associated Renal Vasculitis) study [21] randomized 44 patients with AAV and renal involvement to either receive RTX 375 mg/m2 weekly for 4 doses in addition to steroids and 2 doses of intravenous cyclophosphamide or to conventional therapy, including steroids, cyclophosphamide for 3-6 months, and azathioprine maintenance.…”
Section: Anti-neutrophil Cytoplasmic Antibody (Anca)-associated Smallmentioning
confidence: 99%
“…The RITUXVAS (RTX versus Cyclophosphamide in ANCA-Associated Renal Vasculitis) study [21] randomized 44 patients with AAV and renal involvement to either receive RTX 375 mg/m2 weekly for 4 doses in addition to steroids and 2 doses of intravenous cyclophosphamide or to conventional therapy, including steroids, cyclophosphamide for 3-6 months, and azathioprine maintenance. Remission rates (76% in RTX vs. 82% in conventional therapy) and adverse events (42% in RTX vs. 36% in conventional therapy) were similar in both groups.…”
Section: Anti-neutrophil Cytoplasmic Antibody (Anca)-associated Smallmentioning
confidence: 99%
“…Furthermore, it may be considered particularly in relapsing patients (38,42,43). In a subgroup analysis, RTX at 6 months was found to be superior to CYC in inducing remission in those who relapsed than CYC in patients enrolled in the Rituximab in ANCA-Associated Vasculitis (RAVE) trial (39). Evaluation over a longer period of time of patients in the RAVE trial with severe AAV found that a single course of RTX was as effective as continuous conventional immunosuppressive therapy for induction and maintenance of remission over an 18-month period (44).…”
Section: Discussionmentioning
confidence: 99%